Competition Commission vs South African Airways (2005) - Metton, Eulalie; Luiz, John ([London] : SAGE, 2016)
In July 2005, the BA/Comair (Comair) executives were eagerly awaiting the Competition Tribunal's decision in the case brought by the Competition Commission against South African Airways (SAA). The case had been brought on behalf of the Nationwide Group, a domestic air travel rival to SAA. Nationwide lodged its complaint in October 2000, contending that, since 1999, SAA's incentives schemes to travel agents were so attractive as to force travel agents into selling SAA domestic travel tickets to the exclusion of Nationwide. This text examines how the Tribunal arrived at its verdict.
Originally Published in: Metton, E., & Luiz, J. (2010). Competition Commission Case Series: Competition Commission vs South African Airways (2005). WBS-2010-14c. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; South African Airways; Competition, Unfair -- South Africa -- Cases